Efeitos da dupla tarefa na marcha, no equilíbrio e na cognição em idosos : da avaliação ao treinamento - Andrade, Verônica Filter de (My University, 2026)
Aging is associated with cognitive and motor changes that compromise the ability to manage simultaneous demands and negatively affect functional performance in older adults. Although the dual-task (DT) paradigm has been widely used to investigate the interaction between cognition and movement, studies simultaneously comparing different motor domains across distinct aging contexts and cognitive profiles remain scarce. This thesis investigated the effects of DT on gait, balance, and cognitive performance in older adults, as well as the effects of a training program based on this paradigm. Three complementary studies were conducted: a cross-sectional study involving 21 institutionalized older adults, a correlational study including 62 community-dwelling older women with preserved global cognition, and a controlled pre?post intervention study involving 54 older women. Spatiotemporal gait parameters and single-leg stance balance measures were obtained using an inertial measurement unit (BAIOBIT), while cognitive performance was assessed using the Mini-Mental State Examination (MMSE), verbal fluency tasks, and serial subtraction tasks. All variables were analyzed under both single-task and dual-task conditions. The results demonstrated that DT consistently reduced gait speed and cadence, whereas postural balance showed lower responsiveness to cognitive overload. Among community-dwelling older women, gait speed was significantly associated with cognitive performance, although the correlations were of low magnitude. The high MMSE scores and limited cognitive variability observed in this sample suggest a ceiling effect that may have attenuated the strength of these associations. Nevertheless, the consistency of the findings reinforces the sensitivity of gait speed in detecting subtle interactions between cognition and movement. In institutionalized older adults, cognitive motor interference was primarily reflected in more basic gait parameters, such as cadence and stride time. The DT training program combined with the Mat Pilates method improved cognitive performance under divided-attention conditions and produced specific effects on postural control during situations involving higher attentional demands. The absence of significant changes in gait parameters suggests that the duration of the intervention may have been insufficient to induce measurable motor adaptations. Taken together, the findings demonstrate that incorporating DT conditions into functional assessments enables the identification of impairments that may not be evident under single-task conditions and that gait speed represents a sensitive marker of cognitive-motor interference. From a clinical perspective, the results support the use of DT-based assessments and interventions for the early identification of functional changes and the preservation of functional capacity during aging. [resumo fornecido pelo autor]
O envelhecimento está associado a alterações cognitivas e motoras que comprometem a capacidade de gerenciar demandas simultâneas e impactam a funcionalidade dos idosos. Embora o paradigma de dupla tarefa (DT) seja amplamente utilizado para investigar a interação entre cognição e movimento, ainda são escassos estudos que comparem simultaneamente diferentes domínios motores em distintos contextos de envelhecimento e perfis cognitivos. Esta tese analisou os efeitos da DT sobre a marcha, o equilíbrio e o desempenho cognitivo em idosos, bem como os efeitos de um programa de treinamento baseado nesse paradigma. Foram conduzidos três estudos complementares: um estudo transversal com 21 idosos institucionalizados, um estudo correlacional com 62 mulheres idosas da comunidade com cognição global preservada e um estudo de intervenção controlado pré-pós com 54 mulheres idosas. Os parâmetros espaço-temporais da marcha e as medidas de equilíbrio unipodal foram obtidos por unidade de medida inercial (BAIOBIT), enquanto o desempenho cognitivo foi avaliado pelo Mini Exame do Estado Mental (MEEM), por tarefas de fluência verbal e de subtração seriada. Todas as variáveis foram analisadas em condições de tarefa simples e dupla tarefa. Os resultados demonstraram que a DT reduziu consistentemente a velocidade e a cadência da marcha, enquanto o equilíbrio postural apresentou menor responsividade à sobrecarga cognitiva. Em mulheres idosas da comunidade, a velocidade da marcha apresentou associações significativas, porém de baixa magnitude, com o desempenho cognitivo. A elevada pontuação no MEEM e a reduzida variabilidade cognitiva da amostra sugerem a presença de efeito teto, que pode ter atenuado a força dessas associações. Ainda assim, a consistência dos resultados reforça a sensibilidade da velocidade da marcha para captar interações sutis entre cognição e movimento. Em idosos institucionalizados, a interferência cognitivo-motora manifestou-se principalmente em parâmetros mais básicos da marcha, como a cadência e o tempo de passada. O treinamento em DT associado ao método Mat Pilates promoveu melhorias no desempenho cognitivo sob condições de atenção dividida e efeitos específicos no controle postural em situações de maior demanda atencional. A ausência de alterações nos parâmetros da marcha sugere que a duração do protocolo pode ter sido insuficiente para promover adaptações motoras mensuráveis. De forma integrada, os achados demonstram que a inclusão da DT na avaliação funcional permite identificar comprometimentos não evidentes em tarefas simples e que a velocidade da marcha constitui um marcador sensível da interferência cognitivo-motora. Do ponto de vista clínico, os resultados reforçam o potencial das avaliações e intervenções baseadas em DT para a identificação precoce de alterações funcionais e para a manutenção da funcionalidade no envelhecimento. [resumo fornecido pelo autor]
Keywords: Cognição em idosos; Envelhecimento; Equilíbrio (Fisiologia); Marcha humana; Cognition in old age; Aging; Equilibrium (Physiology); Gait in humans